Why is the future ready for environmental geotechnics?. Issue 2 (18th March 2014) - Mickovski, Slobodan B.
Abstract : The perception of geotechnical problems has, in recent years, been challenged by requirements for balance between traditional engineering and environment-friendly, sustainable solutions. Modern geotechnical engineers have to develop knowledge on the environment surrounding their solutions and thrive within the new discipline of environmental geotechnics. The general trends in the discipline are used as a background to personal experience to establish the place of a generic environmental geotechnics framework within the sustainable development area. Recent developments and potential future trends in areas that could be considered as part of environmental geotechnics are briefly outlined together with the need for training and education.